Circ_0035292 knockdown alleviates lipopolysaccharide (LPS)‐induced WI‐38 cell apoptosis and inflammatory injury - Ying Guo; Zhouzhen Li; Chen Cheng (Immunity, Inflammation and Disease)
Abstract Background Circular RNAs have emerged as important regulators in the pathogenesis of human diseases, including infantile pneumonia (IP). In this study, we aimed to explore the effects of circ_0035292 on lipopolysaccharide (LPS)‐treated Wistsar Institute (WI)‐38 cells. Methods Quantitative real‐time polymerase chain reaction and western blot were executed to detect the levels of circ_0035292, microRNA‐370‐3p (miR‐370‐3p) and transducin β‐like 1X related protein 1 (TBL1XR1). Cell counting kit‐8, 5‐ethynyl‐2′‐deoxyuridine, and flow cytometry assessed cell proliferation and apoptosis. Concentrations of inflammatory factors were examined with enzyme linked immunosorbent assay kits. Dual‐luciferase reporter assay and RNA immunoprecipitation were adopted to analyze binding between miR‐370‐3p and circ_0035292 or TBL1XR1. Results Circ_0035292 level was increased in IP patients and LPS‐triggered WI‐38 cells. Circ_0035292 knockdown rescued LPS‐mediated WI‐38 cell proliferation suppression and WI‐38 cell apoptosis and inflammation promotion. Circ_0035292 interacted with miR‐370‐3p and miR‐370‐3p directly targeted TBL1XR1. Moreover, miR‐370‐3p overexpression alleviated LPS‐induced WI‐38 cell apoptosis and inflammatory injury, which was abrogated via TBL1XR1 upregulation. Circ_0035292 absence inhibited the NF‐κB pathway. Conclusion Knockdown of circ_0035292 rescued LPS‐triggered WI‐38 cell injury via miR‐370‐3p/TBL1XR1 axis and NF‐κB pathway.